Crioconservação de embriões de tambaqui (Colossoma macropomum) - Fornari, Darci Carlos (2012)
Cryopreservation of genetic material of fish has become a tool essential for preservation of biological materials and production. However, stocking of fish embryos in liquid nitrogen (-196°C) and maintain indefinitely is not yet possible. Recently, developments in research on cryopreservation allowed storing embryos at -8°C for 24 hours. This indicates the possibilityof fish embryo cryopreserving, moreover, the biotechnical cooling for a short time already has practical applications. The present study aimed to evaluate the efficiency of different cryoprotectants to the processes of cryopreservation (freezing, vitrification and cooling) of tambaqui embryos (Colossoma macropomum). Despite not having succeeded in tambaqui embryos cryopreservation important points has been clarified as related to damage to the embryos. Injuries and morphological changes in embryos were identified at all stages of the freezing process, being higher with stabilization at -35°C after being submerged in liquid nitrogen and thawed. At the moment of the seeding besides a lower incidence of injuries, higher percentage of embryos with chorion were observed. The freezing curve protocolstested have not prevented the formation of ice crystals, thus turning unfeasible the embryonic embryos C. macropomum freezing. In the experiment of vitrification the methanol 20% with two-minutes of pre-immersion in exposure to liquid nitrogen, preserved the chorion and some cellular structures. Although it avoided further damage was not sufficient to prevent mortality of embryos, these results open perspectives for continued studies on cryopreservation of fish embryos. Ethylene glycol, glycerol and DMSO were toxic at higher concentrations (20 and30%) not being interesting for the vitrification of embryos C. macropomum. In tests of cooling to at -8°C treatments with ethylene glycol, glycerol and DMSO associated withsucrose did not result in satisfactory answers. To store embryos of C. macropomum at -8°Cfor a period of six hours is suggested cryoprotectant solutions with 17% sucrose combinedwith 10% methanol.